Conflict Management Styles of Nurse Managers in Hospitals Affiliated to Tehran University of Medical Sciences: 2015 - AM Mosadeghrad; A Mojbafan (Iran University of Medical Sciences, 2017)
Abstract Background & Aims: Conflict in nursing profession is inevitable and may result in nurses' dissatisfaction and low quality services to patients. Proper management of conflicts in nursing may result in an increase in nursing productivity. The aim of this study was to examine the conflict management strategies used by the nurse managers of educational hospitals affiliated to Tehran University of Medical Sciences. Materials & Methods: It was a descriptive and cross-sectional study, performed in 2015. The statistic population included 269 nurse managers of educational hospitals affiliated to Tehran University of Medical Sciences. The instrument was a self-made questionnaire based on Thomas-Kilmann conflict management model. The SPSS software version 22 was used for statistical analysis of the data, using descriptive and inferential statistics. Results: Nurse managers mainly used collaborating, compromising, and avoiding strategies in management of conflicts. There were significant associations between using collaborating style and nurse managers' age, work experience, conflict management training courses and type of hospitals. Those managers who had higher work experience and passed conflict management training courses, mostly used collaborating style (P<0.05). Conclusion: The nature of nursing services requires nurse managers to apply more collaborating and compromising strategies for conflict resolution. Appointing well-experienced nurses as nurse managers and training them in conflict management reduce destructive consequences of conflicts in hospitals.